Impact of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis) - Gazeau, Frédéric; Alliouane, Samir; Bock, Christian; Bramanti, Lorenzo; López Correa, Matthias; Gentile, Miriam; Hirse, Timo; Pörtner, Hans-Otto; Ziveri, Patrizia (Frontiers in Marine Science, 2014)
In order to assess the effects of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis), specimens were reared in aquarium tanks and exposed to elevated conditions of temperature (+3 °C) and acidity (-0.3 pH units) for a period of 10 months. The whole system comprised a factorial experimental design with 4 treatments (3 aquaria per treatment): control, lowered pH, elevated temperature and lowered pH/elevated temperature. Mortality was estimated on a weekly basis and every 2 months, various biometrical parameters and physiological processes were measured: somatic and shell growth, metabolic rates and body fluid acid-base parameters. Mussels were highly sensitive to warming, with 100 % mortality observed under elevated temperature at the end of our experiment in October. Mortality rates increased drastically in summer, when water temperature exceeded 25 °C. In contrast, our results suggest that survival of this species will not be affected by a pH decrease of ~0.3 in the Mediterranean Sea. Somatic and shell growth did not appear very sensitive to ocean acidification and warming during most of the experiment, but were reduced, after summer, in the lowered pH treatment. This was consistent with measured shell net dissolution and observed loss of periostracum, as well as uncompensated extracellular acidosis in the lowered pH treatment indicating a progressive insufficiency in acid-base regulation capacity. However, based on the present dataset, we cannot elucidate if these decreases in growth and regulation capacities after summer are a consequence of lower pH levels during that period or a consequence of a combined effect of acidification and warming. To summarize, while ocean acidification will potentially contribute to lower growth rates, especially in summer when mussels are exposed to sub-optimal conditions, ocean warming will likely pose more serious threats to Mediterranean mussels in this region in the coming decades.